A new species of Pronura (Neanuridae: Paleonurini) from the Luquillo Mountains, Puerto Rico with a key to American poorly tuberculated Paleonurini - Ospina-Sánchez, Claudia M.; Palacios-Vargas, José G.; González, Grizelle (Zootaxa, 2021)
A new species of Pronura from the Luquillo Experimental Forest on Northeastern Puerto Rico is described and illustrated. Pronura yunquensis sp. nov. differs from other Neotropical Pronura in the absence of eyes and can be separated from other species of the genus by the presence of a head tubercle (De), the displacement of Di1 in Abd IV and the fused tubercles De+DL in Abd V. A key for identification to American species of Paramanura, Pronura and Paleonura is included.